THE PERFORMANCE OF GO PUBLIC BANK IN INDONESIA: BEFORE AND DURING COVID-19 - Okta Sindhu Hartadinata; Elva Farihah (Berkala Akuntansi dan Keuangan Indonesia, 2021)
This study aims to examine differences in the performance of banks listed on the Indonesia Stock Exchange before the COVID-19 pandemic in 2019 and during the COVID-19 pandemic in 2020. The type of data collected is quantitative data. The data source used is secondary data derived from data on financial statements of banking companies listed on the Indonesia Stock Exchange for the period 2019-2020. The analytical technique used is a different test, paired sample t test with a significance level of 5%. The results showed that the government policy POJK 11/POJK.03/2020 regarding credit restructuring which was later extended by POJK 48/POJK.03/2020 and POJK 12/POJK.03/2020 greatly affected the stability of bank performance.